Early identification of individuals at risk for multiple sclerosis by quantification of EBNA-1381-452-specific antibody titers - Hannes Vietzen; Laura M. Kühner; Sarah M. Berger; Markus Ponleitner; Marianne Graninger; Charlotte Pistorius; Christof Jungbauer; Markus Reindl; Henrieke Saucke; Franziska Kauth; Eva-Maria Wendel; Kevin Rostásy; et al. (Nature Communications)
Abstract Multiple sclerosis (MS) is an immune-mediated demyelinating disease. Epstein-Barr virus (EBV) encodes for the EBNA-1381-452 region that induces autoreactive antibody responses, which are likely critically involved in MS pathogenesis. Here we investigate whether these EBNA-1381-452-specific antibodies can serve as a biomarker to identify at-risk individuals for MS. We quantify EBNA-1381-452-specific antibody titers from 324 relapsing-remitting MS patients and 324 matched controls in longitudinal follow-up plasma samples, starting from the individual’s EBV-seroconversion. In MS patients, significantly elevated EBNA-1381-452-specific IgG titers are identified that are increased already as early as nine months after EBV-seroconversion (OR:5.7; 95% CI: 4.1-8.1; P < 0.0001) and a median 5.4 years prior to MS diagnosis. Especially, the presence of continuously high EBNA-1381-452-specific antibody titers is associated with a more rapid MS diagnosis after EBV-seroconversion (P < 0.0001). Thus, the quantification of EBNA-1381-452-specific IgG antibody levels may provide a prognostic biomarker to determine the individual’s risk for the diagnosis of MS.